Evidence for circadian-based photoperiodic timekeeping in Svalbard ptarmigan, the northernmost resident bird - Appenroth, Daniel; Wagner, Gabriela; Hazlerigg, David; West, Alexander Christopher (Current Biology, 2021)
The high Arctic archipelago of Svalbard (74°–81° north) experiences extended periods of uninterrupted daylight in summer and uninterrupted night in winter, apparently relaxing the major driver for the evolution of circadian rhythmicity. Svalbard ptarmigan ( Lagopus muta hyperborea ) is the only year-round resident terrestrial bird species endemic to the high Arctic and is remarkably adapted to the extreme annual variation in environmental conditions. Here, we demonstrate that, although circadian control of behavior disappears rapidly upon transfer to constant light conditions, consistent with the loss of daily activity patterns observed during the polar summer and polar night, Svalbard ptarmigans nonetheless employ a circadian-based mechanism for photoperiodic timekeeping. First, we show the persistence of rhythmic clock gene expression under constant light within the mediobasal hypothalamus and pars tuberalis, the key tissues in the seasonal neuroendocrine cascade. We then employ a “sliding skeleton photoperiod” protocol, revealing that the driving force behind seasonal biology of the Svalbard ptarmigan is rhythmic sensitivity to light, a feature that depends on a functioning circadian rhythm. Hence, the unusual selective pressures of life in the high Arctic have favored decoupling of the circadian clock from organization of daily activity patterns, while preserving its importance for seasonal synchronization.